Tensile behaviour of kenaf fiber reinforced polymer composites - Hafizah, N.; Hussin, M.; Jamaludin, M.; Bhutta, M.; Ismail, Mohamed; Azman, M. (Penerbit Universiti Teknologi Malaysia, 2014)
Natural fiber is usually used as reinforcement in polymeric materials, and short fibers are commonly used for non-structural applications. However, the lack of studies on long fiber reinforced polymeric materials, especially kenaf fiber, has limited its usage in Malaysia. This paper presents the experimental results of a series of tensile tests conducted on continuous kenaf fibers produced with different types of thermoset resin (epoxy, polyester, and vinyl ester) arranged longitudinally. A total of 75 kenaf fiber reinforced polymer composites containing up to 50% fiber volume fraction including 15 neat samples as control samples were produced. Then, the samples were tested using Universal Testing Machine to obtain their tensile behaviour. Results indicated that the composites' performance increased gradually with every increment of fiber volume fraction. Factors affecting the tensile behaviour of kenaf fiber reinforced polymers are also explained and discussed. In conclusion, kenaf fiber can be used as reinforcing materials in polymeric materials. © 2014 Penerbit UTM Press. All rights reserved.